2010
DOI: 10.1007/s11926-010-0119-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Myopathies

Abstract: We consider recent developments in disorders affecting three areas of metabolism: glycogen, fatty acids, and the mitochondrial respiratory chain. Among the glycogenoses, new attention has been directed to defects of glycogen synthesis resulting in absence rather than excess of muscle glycogen ("aglycogenosis"). These include defects of glycogen synthetase and defects of glycogenin, the primer of glycogen synthesis. Considerable progress also has been made in our understanding of alterations of glycogen metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 49 publications
0
16
0
2
Order By: Relevance
“…The significance of diseases with mitochondrial basis, including adverse pregnancy complications, such as placental abruption and preeclampsia (6, 20), motivate the need to understand common genetic variations that underlie mtDNA copy number, a trait that reflects mitochondrial dysfunction (13). The first GWAS study in 2012 that identified nuclear DNA variation that may influence mtDNA levels (measured as the ratio of mtDNA quantity to nuclear DNA quantity, mtDNA/nDNA) was conducted among 386 Spanish families of the GAIT (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of diseases with mitochondrial basis, including adverse pregnancy complications, such as placental abruption and preeclampsia (6, 20), motivate the need to understand common genetic variations that underlie mtDNA copy number, a trait that reflects mitochondrial dysfunction (13). The first GWAS study in 2012 that identified nuclear DNA variation that may influence mtDNA levels (measured as the ratio of mtDNA quantity to nuclear DNA quantity, mtDNA/nDNA) was conducted among 386 Spanish families of the GAIT (21).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction underlies cardiometabolic disorders, neurodegenerative disease and cancer (13). Accumulating evidence, including work from our group, supports the role of mitochondrial dysfunction in adverse pregnancy complications (48).…”
Section: Introductionmentioning
confidence: 99%
“…The sample revealed ragged‐red fibers. The patient was diagnosed with Kearns‐Sayre syndrome (KSS) with mitochondrial gene mutation at position 3243 (1, 3–7). There was a reduction in mitochondrial respiratory chain complexes I and III.…”
Section: Case Reportsmentioning
confidence: 99%
“…Metabolic myopathies consist of inborn errors of glycogen, lipid, and mitochondrial respiratory chain enzymes (1). They result in weakness with or without muscle breakdown and in the case of mitochondrial disease, a bewildering array of multisystem abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations of mitochondrial homeostasis and integrity lead to severe pathophysiological consequences and the onset of disease. Numerous studies implicate mitochondrial dysfunction as an underlying factor of multiple pathologies in humans, including cardiovascular disorders, myopathies, certain cancers, type II diabetes, and neurological and neurodegenerative diseases (23,36,50,95,104,115,130,141,149,157,179,188). These maladies become particularly prevalent as people age and have been linked with age-associated decline in mitochondrial health (18,95,115,157).…”
mentioning
confidence: 99%